2020
DOI: 10.1159/000506591
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Perfusion Computed Tomography Imaging in Patients with Seizures Mimicking Acute Stroke

Abstract: Introduction: Seizures as acute stroke mimics are a diagnostic challenge. Objective: The aim of the study was to characterize the perfusion patterns on perfusion computed tomography (PCT) in patients with seizures masquerading as acute stroke. Methods: We conducted a study on patients with acute seizures as stroke mimics. The inclusion criteria for this study were patients (1) initially presenting with stroke-like symptoms but finally diagnosed to have seizures and (2) with PCT performed within 72 h of seizure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…11 Furthermore, the availability of PCT in SM has led to the characterization of PCT alterations in SM, especially in epileptic seizures, that can be useful in the differential diagnosis of stroke. 12 Cortical spreading depression (CSD) has been proposed as the pathophysiological basis of migraine aura, a state of spreading electrical discharge and depolarization of neurons and glia followed by complete recovery of cortical electrical activity. The depolarization wave causes vasodilation and an increase in regional cerebral blood flow (CBF), which has been termed spreading hyperemia, followed by a prolonged period of hypoperfusion lasting 1-2 h, called spreading oligemia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Furthermore, the availability of PCT in SM has led to the characterization of PCT alterations in SM, especially in epileptic seizures, that can be useful in the differential diagnosis of stroke. 12 Cortical spreading depression (CSD) has been proposed as the pathophysiological basis of migraine aura, a state of spreading electrical discharge and depolarization of neurons and glia followed by complete recovery of cortical electrical activity. The depolarization wave causes vasodilation and an increase in regional cerebral blood flow (CBF), which has been termed spreading hyperemia, followed by a prolonged period of hypoperfusion lasting 1-2 h, called spreading oligemia.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, multimodal computed tomography (CT) including PCT has become an important tool for decision‐making in acute ischemic stroke and has been included as part of the SC protocol at many centers 11 . Furthermore, the availability of PCT in SM has led to the characterization of PCT alterations in SM, especially in epileptic seizures, that can be useful in the differential diagnosis of stroke 12 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, epileptic disorders were also the most prevalent diagnosis amongst patients with PCT alterations. Previous studies have proved the utility of PCT in the diagnosis of SMs [11] especially in the ictal phase of seizures with regard to CBV [27,30]. Moreover, studies have shown that PCT abnormalities are relatively common in patients soon after seizure [31].…”
Section: Discussionmentioning
confidence: 99%
“…Both hypoperfusion and hyperperfusion patterns have been found in seizures [42]. Moreover, a hyperperfusion pattern demonstrating an increase in CBV has been found to be useful in differentiating seizures from strokes [27,30]. However, the general distribution of PCT alteration patterns in SMs has not been described in detail in complete series of SMs.…”
Section: Discussionmentioning
confidence: 99%
“…According to two studies, time to peak (TTP) can be used as a sensitive measure for differentiating stroke and seizure. 40,41 Kubiak-Balcerewicz and colleagues found that the value of asymmetry index for TTP (1.23%) in the lateral part of the MCA territory could discriminate patients with stroke and seizure. This finding, however, was not of clinical significance according to the authors.…”
Section: Seizurementioning
confidence: 99%